Jabatan Penyiaran Negeri Pahang / Nur Fathiah Mohamed - Mohamed, Nur Fathiah (Universiti Teknologi MARA, Perlis, 2023)
This report is prepared for the internship phase of The Bachelor of Business Administration (Hons.) Human Resource Management program. This very meaningful industrial training experience started at the Jabatan Penyiaran Negeri Pahang (RTM Pahang) for six months from 1 March 2023 until 15 August 2023. This report was also prepared based on my observations and experiences during my time here. This department is located in Kuantan, Pahang which operates Monday to Friday only for the management and administration section while the radio broadcasting section operates every day. Throughout my time here I have been exposed to various knowledge and have been able to experience various experiences as a citizen of RTM Pahang. Here I was treated very well and like family. I was selected to be placed in the administration and management department. I have been given several tasks such as managing phone calls, managing administrative matters, preparing documents such as meeting minutes and using new software. The assignments given can give me a lot of new knowledge and learning. This report contains five important parts which are student profile, company profile, training reflection, SWOT analysis as well as discussion and recommendations.